The Effect of Minimum Wage, Gross Regional Domestic Product (GRDP) and Open Unemployment Rate on Labor Absorption in Manufacturing Industry Sector in Java Island - Rebion Raga Munggaran; Asep Munir Hidayat; Billy Tejaarief; Kenedi Kenedi; Anti Wulan Agustini (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2025)
The manufacturing industry in Java Island plays an important role in Indonesia's economy, contributing significantly to Minimum Wage, Gross Regional Domestic Product, and Open Unemployment Rate. However, there are imbalances between provinces influenced by regional policies, economic conditions, and industrial sectors. This research aims to analyze the long-term, short-term effects, and long-term adjustment mechanism (Error Correction Term) in Java Island, covering six provinces: DKI Jakarta, West Java, Central Java, DI Yogyakarta, East Java, and Banten. The method used is a quantitative approach with secondary data from Statistics Indonesia (BPS) for the period 2010-2024, analyzed using Panel Autoregressive Distributed Lag (ARDL) model with EViews version 13 software. The research results show that in the long term, Minimum Wage and Open Unemployment Rate have significant negative effects on Labor Absorption, while Gross Regional Domestic Product has a significant positive effect. In the short term, these variables do not significantly affect most provinces. However, analysis of the long-term adjustment mechanism (Error Correction Term) shows that provinces such as West Java, DI Yogyakarta, East Java, and Banten have significant adjustments, while DKI Jakarta and Central Java do not show significant adjustments. The research conclusions indicate that Gross Regional Domestic Product has a positive effect on labor absorption, while Minimum Wage and Open Unemployment Rate have negative effects. Long-term adjustment mechanisms are significant in several provinces, but DKI Jakarta and Central Java face structural barriers. Therefore, more responsive and balanced economic policies are needed.